2006
DOI: 10.4049/jimmunol.177.11.7634
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tolerance Induction with Antigen Conjugated to Cholera Toxin B Subunit Generates Both Foxp3+CD25+ and Foxp3−CD25− CD4+ Regulatory T Cells

Abstract: Oral administration of Ag coupled to cholera toxin B subunit (CTB) efficiently induces peripheral immunological tolerance. We investigated the extent to which this oral tolerance is mediated by CD25+CD4+ regulatory T cells (Treg). We found that total Treg, KJ1–26+ Treg and CTLA-4+ Treg were all increased in Peyer’s patches, mesenteric lymph nodes, and, to a lesser extent, in spleen of mice after intragastric administration of OVA/CTB conjugate, which also increased TGF-β in serum. This could be abolished by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 40 publications
(54 reference statements)
10
93
0
Order By: Relevance
“…In fact, rice seed containing CTB-fused allergen-specific T cell epitopes induces oral tolerance to allergen more efficiently than does rice expressing allergen-specific epitopes alone (34). Moreover, conjugation of an antigen to CTB can induce the proliferation of regulatory T cells (35,36); this may be the mechanism by which the above mentioned rice seed containing the CTB-fused epitopes effectively induces oral tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, rice seed containing CTB-fused allergen-specific T cell epitopes induces oral tolerance to allergen more efficiently than does rice expressing allergen-specific epitopes alone (34). Moreover, conjugation of an antigen to CTB can induce the proliferation of regulatory T cells (35,36); this may be the mechanism by which the above mentioned rice seed containing the CTB-fused epitopes effectively induces oral tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that intragastric, s.l., or intranasal mucosal administration of OVA and other Ags in mice, given alone or with increased efficiency when linked to CTB, can induce peripheral T cell tolerance ("oral tolerance") along with Ag-specific Tregs (8,9). We examined whether FcgRIIB is required for such mucosal induction of tolerance, initially by comparing the effect on the development of DTH in FcgRIIB 2/2 mice and WT mice after s.l.…”
Section: Resultsmentioning
confidence: 99%
“…We (3)(4)(5) and other investigators (6)(7)(8) demonstrated that mucosal administration of various types of Ags coupled to cholera toxin B subunit (Ag/CTB) by either chemical conjugation or genetic fusion can more efficiently, and at .100-fold reduced dosages compared with Ag alone or Ag mixed with cholera toxin B subunit (CTB), induce peripheral T cell tolerance. Similar to other low-dose tolerance, this effect is associated with induction of Foxp3 + , as well as Foxp3 2 , Tregs (9). The coupling of Ag to CTB, which binds to GM1 ganglioside receptors present on many cell types, including all known APCs, strongly potentiates the mucosal tolerizing effect (10) by facilitating Ag transport across the mucosal barrier and, more importantly, increasing Ag uptake and presentation by APCs, such as dendritic cells (DCs), B cells, and macrophages (11,12).…”
mentioning
confidence: 86%
See 2 more Smart Citations